Momentum Distribution Functions in a One-Dimensional Extended Periodic Anderson Model. (20th September 2015) - Hagymási, I.; Sólyom, J.; Legeza, Ö.
Abstract : We study the momentum distribution of the electrons in an extended periodic Anderson model, where the interaction, U c f, between itinerant and localized electrons is taken into account. In the symmetric half-filled model, due to the increase of the interorbital interaction, thef electrons become more and more delocalized, while the itinerancy of conduction electrons decreases. Above a certain value ofU c f thef electrons become again localized together with the conduction electrons. In the less than half-filled case, we observe thatU c f causes strong correlations between thef electrons in the mixed valence regime.